Geography, Institutions and Principles. Bits and Pieces of Empirical Evidence from Small-scale Banking - Franz R. Hahn (Austrian Institute of Economic Research (WIFO), 2011)
Theory suggests that the cross-border bank lending flow from rich countries to poor countries is facilitated when lending-related legal and social norms are shared and valued equally by both lenders and borrowers. According to this reasoning the fast adoption of Western-style democracy and market economy principles as established by EU standards by many of the East European "transformation countries" since the early 1990s should have raised cross-border lending by banks based in EU 15 countries to clients resident in new East European EU member countries. Exploring cross-border lending activities of Austrian small- to medium-sized regional banks over the period from 1995 to 2008 with panel and spatial econometric techniques this paper provides evidence that is supportive of this presumption.
Keywords: 330; panel econometric analysis; spatial econometric analysis; cross-border bank lending; institutions; neoclassical economics; Internationale Bank; Österreich; Bankgeschäft; EU-Mitgliedschaft